8.0k views
3 votes
X - 5 + 12 + 2x = 4(8 – 11x) + 7(1 + 9x)

User Atypical
by
6.6k points

2 Answers

6 votes

Answer:

x = -2

Explanation:

x - 5 + 12 + 2x = 4(8 – 11x) + 7(1 + 9x)

x - 5 + 12 + 2x = 32 - 44x + 7 + 63x

x - 5 + 12 + 2x = 32 - 44x + 7 + 63x

x + 2x + 44x - 63x = 32 + 7 + 5 - 12

- 16x = 32

- x = 32 / 16

- x = 2

x = -2

User Alioygur
by
6.2k points
2 votes

Answer:

Isolate the variable by dividing each side by factors that don't contain the variable. x= -2

User Joppo
by
5.8k points